2022
DOI: 10.1002/hep4.2013
|View full text |Cite
|
Sign up to set email alerts
|

GCKIII kinases in lipotoxicity: Roles in NAFLD and beyond

Abstract: Nonalcoholic fatty liver disease (NAFLD) is defined by excessive accumulation of lipid droplets within hepatocytes. The STE20-type kinases comprising the germinal center kinase III (GCKIII) subfamily -MST3, MST4, and STK25 -decorate intrahepatocellular lipid droplets and have recently emerged as critical regulators of the initiation and progression of NAFLD. While significant advancement has been made toward deciphering the role of GCKIII kinases in hepatic fat accumulation (i.e., steatosis) as well as the agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Mechanistic analysis revealed that a lack of MST3 in both cultured liver cells and the livers of animals after HFD activates the insulin signaling pathway downstream of IRS1 by inhibiting forkhead box (FOX)O1-mediated downregulation of genes encoding gluconeogenic enzymes [ 40 ]. In addition to the regulation of insulin signaling, studies have reported that MST3, MST4, and STK25 are exclusively localized around intracellular lipid droplets and increase fat accumulation in human hepatocytes as well as the initiation and progression of nonalcoholic fatty liver disease (NAFLD) [ 9 , 41 ]. Mice treated with antisense oligonucleotides (ASOs) targeting MST3 effectively ameliorated HFD-induced nonalcoholic fatty liver disease (NAFLD)-associated liver steatosis, inflammation, fibrosis, and hepatocellular damage [ 41 ].…”
Section: Roles and Regulatory Mechanisms Of Mst3 In Disease Progressionmentioning
confidence: 99%
“…Mechanistic analysis revealed that a lack of MST3 in both cultured liver cells and the livers of animals after HFD activates the insulin signaling pathway downstream of IRS1 by inhibiting forkhead box (FOX)O1-mediated downregulation of genes encoding gluconeogenic enzymes [ 40 ]. In addition to the regulation of insulin signaling, studies have reported that MST3, MST4, and STK25 are exclusively localized around intracellular lipid droplets and increase fat accumulation in human hepatocytes as well as the initiation and progression of nonalcoholic fatty liver disease (NAFLD) [ 9 , 41 ]. Mice treated with antisense oligonucleotides (ASOs) targeting MST3 effectively ameliorated HFD-induced nonalcoholic fatty liver disease (NAFLD)-associated liver steatosis, inflammation, fibrosis, and hepatocellular damage [ 41 ].…”
Section: Roles and Regulatory Mechanisms Of Mst3 In Disease Progressionmentioning
confidence: 99%
“…Serine/threonine protein kinase 25 (STK25), a member of the GCKIII, has been identified as a critical regulator of ectopic lipid storage, glucose and insulin homeostasis, fibrosis, and meta-inflammation. In humans, STK25 is located on chromosome 2q37.3 [4]. The important role of STK25 is to participate in autophagy, cell polarity, cell apoptosis, and cell migration.…”
Section: Composition Of Stk25mentioning
confidence: 99%
“…These kinases decorate lipid droplets in hepatic cells, and the expression of GCKIII kinases in the liver is associated with the severity of NAFLD. The suppression of STK24, MST4, and STK25 dramatically decreased intracellular lipid accumulation in human hepatocytes (Mahlapuu et al, 2022). STK24 promotes IL‐17‐mediated inflammation (Jiang et al, 2018) and is upregulated in human hepatocellular carcinoma tissues (Caputo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%